Inequality and social protection at the local level: Undermining or reinforcing social policy? - Skamnakis, Christoforos (The Greek Review of Social Research, 2011)
Inequality is an interdisciplinary issue shaped at supranational, national and regional or local level. Public policies in tackling inequality are regulated under pressures produced by global conjuncture and the way that these are affecting national welfare arrangements. Local authorities increasingly implement social protection interventions across Europe, as local distributors of state’s policies. In Greece, in the field of local government have taken place major reforms the last three decades. Responsibilities of local authorities have widened, especially in the field of social protection, based mainly on EU’s Structural Funds. In the current conjuncture of fiscal austerity and deregulation of the -weak anyway- welfare state in general social policy seems to be squashed in between the supra national factor on one side and subnational on the other.